The Impact of Asian Financial Crisis on Bank: Empirical Evidence from Thailand and Malaysia - Sufian, Fadzlan; Habibullah, Muzafar Shah (Giordano Dell'Amore Foundation, Italy, 2009)
By using bank level data this paper examines how bank specific characteristics and the macroeconomic environment affects the profitability of the Thailand and Malaysian banking sectors over the period 1992-2003. All the variables are significant although their impact is not always the same for Thailand and Malaysian banks. We find that liquidity is negatively related to Thailand banks’ profitability, but not in Malaysia, while network embeddedness has negative relationship with Malaysian banks, but not Thailand banks. As for the impact of macroeconomic indicators, we find that economic growth is positively related to Thailand banks’ profitability only during the pre-crisis period. The impact of inflation is positive on Thailand banks’ profitability during the crisis and post-crisis periods, while inflation is negatively related to Malaysian banks’ profitability during the crisis period. We find that the Thailand banking sector has been relatively more profitable during the pre-crisis period, while the opposite is true for the Malaysian banking sector.